2018
DOI: 10.1089/cmb.2017.0218
|View full text |Cite
|
Sign up to set email alerts
|

Viral Capsid Assembly: A Quantified Uncertainty Approach

Abstract: Most of the existing research in assembly pathway prediction/analysis of viral capsids makes the simplifying assumption that the configuration of the intermediate states can be extracted directly from the final configuration of the entire capsid. This assumption does not take into account the conformational changes of the constituent proteins as well as minor changes to the binding interfaces that continue throughout the assembly process until stabilization. This article presents a statistical-ensemble-based a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…We showed that, under this simplified model of small perturbations, there can be a wide variance in simple QOI. In [13], we further showed that perturbations under this simplistic model can propagate to further uncertainties in the viral assembly problem.…”
Section: Uncertainty Quantificationmentioning
confidence: 77%
“…We showed that, under this simplified model of small perturbations, there can be a wide variance in simple QOI. In [13], we further showed that perturbations under this simplistic model can propagate to further uncertainties in the viral assembly problem.…”
Section: Uncertainty Quantificationmentioning
confidence: 77%
“…The present work focuses on fixed structures for the dimer subunits of cowpea chlorotic mottle virus (CCMV) formed from the A − B and C − C chains (PDB 1za7, [ 40 ]), as well as a model of the pentamer subunits of generic dodecamer assembly. Clement et al [ 41 ] examines the energetic effects of allowing the subunits to come from a distribution of possible configurations rather than a single PDB structure.…”
Section: Methodsmentioning
confidence: 99%
“…However, other optimization approaches can be employed when the measurement matrix is highly coherent when 1 minimization is not necessarily optimal. Finally, it would be interesting to employ the developed DSRAR approach for UQ study in other complex biological systems [94,95]. Such results will be presented in a future publication.…”
Section: Uq Study Of a Molecule System Under Non-gaussian Conformatio...mentioning
confidence: 96%